2022
DOI: 10.3389/frai.2022.796793
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Representations of Individual Entities in the Brain Combining EEG and Distributional Semantics

Abstract: Semantic knowledge about individual entities (i.e., the referents of proper names such as Jacinta Ardern) is fine-grained, episodic, and strongly social in nature, when compared with knowledge about generic entities (the referents of common nouns such as politician). We investigate the semantic representations of individual entities in the brain; and for the first time we approach this question using both neural data, in the form of newly-acquired EEG data, and distributional models of word meaning, employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 191 publications
(281 reference statements)
1
6
0
Order By: Relevance
“…Modification of the semantic representations through semantic composition is the raison d'être of contextualized language models, which represent each word as a complex, nonlinear function of the other words surrounding them. Furthermore, our pattern of results is consistent with recent results in the literature which clearly indicates that contextualized language models provide excellent fit with brain data (Anderson et al., 2021; Bruera & Poesio, 2022; Caucheteux & King, 2022; Goldstein et al., 2022; Jat et al., 2019; Sun, Wang, Zhang, & Zong, 2020; Schrimpf et al., 2021). Note, however, that these previous works only considered either simple concepts or longer, less controlled sentences, while our work focused on an intermediate unit—phrases—and involved much more stringent testing: we used a strictly controlled modulation of concreteness and very specific cases of verb‐noun composition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Modification of the semantic representations through semantic composition is the raison d'être of contextualized language models, which represent each word as a complex, nonlinear function of the other words surrounding them. Furthermore, our pattern of results is consistent with recent results in the literature which clearly indicates that contextualized language models provide excellent fit with brain data (Anderson et al., 2021; Bruera & Poesio, 2022; Caucheteux & King, 2022; Goldstein et al., 2022; Jat et al., 2019; Sun, Wang, Zhang, & Zong, 2020; Schrimpf et al., 2021). Note, however, that these previous works only considered either simple concepts or longer, less controlled sentences, while our work focused on an intermediate unit—phrases—and involved much more stringent testing: we used a strictly controlled modulation of concreteness and very specific cases of verb‐noun composition.…”
Section: Discussionsupporting
confidence: 91%
“…Note that, each round of pairwise evaluations measures to what extent the model has learnt to generalize in the specific case of the categorical relation holding between the two test items (Bruera & Poesio, 2022; Chyzhyk, Varoquaux, Milham, & Thirion, 2022; Elangovan, He, & Verspoor, 2021; Grootswagers et al., 2017; Gorman & Bedrick, 2019; Lake & Baroni, 2018). Therefore, it is possible to examine the results of different categorical relations separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected, according to previous literature (Proverbio et al, 2001;Bruera & Poesio, 2022) , to be able to decode information about semantic categories for both people and places within the N400 time range, distributed over centrotemporal electrodes.…”
Section: Decoding Analysesmentioning
confidence: 98%
“…Since the range of semantic phenomena affecting the N400 is extremely broad, a unified theoretical account of the N400 as a marker of semantic processing is still missing (Rabovsky, Hansen, & McClelland, 2018;Delogu, Brouwer, & Crocker, 2019;Eddine, Brothers, & Kuperberg, 2022;Šoškić, Jovanović, Styles, Kappenman, & Ković, 2022) . However, crucially for our focus, a number of previous studies found that the time range of the N400 can be modulated by various types of aspects of semantic processing of individual entities -including the ones modulated in our experiment: categorical information (Bruera & Poesio, 2022) ; face familiarity, since a familiarity-induced counterpart of the N400, the FN400, has also been observed (Curran & Hancock, 2007) (although it's not clear whether the two are actually functionally identical or not (Voss & Federmeier, 2011;Bridger, Bader, Kriukova, Unger, & Mecklinger, 2012;Leynes, Bruett, Krizan, & Veloso, 2017)) ; and additionally, the difference between proper names and common nouns (Proverbio, Lilli, Semenza, & Zani, 2001;Proverbio, Mariani, Zani, & Adorni, 2009;Adorni, Manfredi, & Proverbio, 2014;Sulpizio & Job, 2018) .…”
Section: Introductionmentioning
confidence: 93%